Environmental impact assessment of river sand and their alternatives in construction - Vemula Jahnavi (Nanyang Technological University, 2020)
River sand is a crucial material used to make cement in the construction industry due to its unique properties formed naturally. However, river sand mining leads to several harmful environmental impacts. This study aims to find a suitable and feasible alternative to River sand with similar or better properties and helps to lessen these environmental impacts. The alternatives explored in this study, are manufactured sand, crushed waste glass and furnace bottom ash. Production process flow for each material is explained to understand how the material can be made suitable as a construction material. The study uses the ReCiPe midpoint method (H) under Life Cycle Assessment which assesses the environmental impacts under 18 specified impact categories. Environmental Impact Assessment is conducted to assess 1 tonne of each material production. From the results obtained, it can be concluded that crushed waste glass is suitable for partial replacement and manufactured sand is suitable for replacement of river sand, as they contribute lesser to the environmental impact categories when compared to furnace bottom ash. While Furnace bottom ash is feasible to replace river sand due to its properties and the tests, it contributes higher environmental impacts comparatively to river sand and hence, not recommended as a suitable alternative in this study.